2022
DOI: 10.1039/d2em00118g
|View full text |Cite
|
Sign up to set email alerts
|

Atom probe tomography and transmission electron microscopy: a powerful combination to characterize the speciation and distribution of Cu in organic matter

Abstract: The large surface areas in porous organic matter (OM) and on the surface of altered minerals control the sequestration of metal(loid)s in contaminated soils and sediments. This study explores the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The observed Ag NPs may also originate from the patio process but can be also the product of the interaction of Ag + with reduced functional groups of organic matter (dissolved or particulate). [38][39][40] Mercury and Ag are both chalcophile elements and thus Ag-and Hg-bearing ionic species and NPs undergo suldation through their interaction with sulde-species under either aerobic or anaerobic conditions, resulting in the formation of Ag 2 S and HgS NPs. 41 Here, we will focus on the formation of HgS NPs as their formation and stability is important with respect to the later discussion on the potential contribution of released HgS NPs to the observed elevated concentrations of GEM in the GMD and to the potential formation of methylmercury.…”
Section: Formation Of the Hg-ag-bearing Phasesmentioning
confidence: 99%
“…The observed Ag NPs may also originate from the patio process but can be also the product of the interaction of Ag + with reduced functional groups of organic matter (dissolved or particulate). [38][39][40] Mercury and Ag are both chalcophile elements and thus Ag-and Hg-bearing ionic species and NPs undergo suldation through their interaction with sulde-species under either aerobic or anaerobic conditions, resulting in the formation of Ag 2 S and HgS NPs. 41 Here, we will focus on the formation of HgS NPs as their formation and stability is important with respect to the later discussion on the potential contribution of released HgS NPs to the observed elevated concentrations of GEM in the GMD and to the potential formation of methylmercury.…”
Section: Formation Of the Hg-ag-bearing Phasesmentioning
confidence: 99%
“…Since APT compositional analysis relies on time-of-ight mass spectrometry, mass spectral peaks can correspond to species of different atomic identities and mass-to-charge state ratio overlap. For example, 56 Fe 2+ (27.97 Da) and 32 S 2+ (15.99 Da) species overlap with 28 Si 1+ (27.98 Da) and 16 O 1+ (16.00 Da) species, respectively. Hence, only peaks without any overlap between different species present in the sample were selected for each element (Fig.…”
Section: Examinations At the Micrometer-to Atomic-scalementioning
confidence: 99%
“…11 For example, the formation of Cu-bearing NPs in OM has been explored in numerous studies. 12–17 Here, Jadoon and Schindler 17 and Jadoon et al 16 showed that Cu-sulfides and -oxide NPs preferentially form along interfaces of OM and mineral inclusions such as Fe-oxides and silica. However, the formation mechanisms of metal(loid)-bearing NPs in OM and the role of mineral inclusions in these processes are still unknown for many elements including the common contaminants Ag and As.…”
Section: Introductionmentioning
confidence: 97%